MEMPERTIMBANGKAN MODEL DIALOG STRATEGIS DALAM MEMBANGUN SISTEM DAFTAR PEMILIH TETAP (DPT) YANG LEBIH BAIK* - Ryan Saputra Alam; Saiful Wathan (Scientia Integritas Utama, 2022)
The chaotic occurrence of permanent voter lists (DPT) in several general elections (elections) must be handled by implementing an integrated and integrated e-Government. Based on the literature study, it can be concluded that the electronic DPT has been built only based on a narrow view of E-Government, which only seems to be a collection of hardware, software, data, and procedures. It takes a strategy in the form of a strategic dialogue model that emphasizes the central role of humans and humanity, which is one of the keys to the successful implementation of MIS in the E-Government.